2001
DOI: 10.1614/0890-037x(2001)015[0813:moalop]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Action, Localization of Production, Chemical Nature, and Activity of Sorgoleone: A Potent PSII Inhibitor in Sorghum spp. Root Exudates1

Abstract: The root exudates produced by sorghums contain a biologically active constituent known as sorgoleone. Seven sorghum accessions were evaluated for their exudate components. Except for johnsongrass, which yielded 14.8 mg root exudate/g fresh root wt, sorghum accessions consistently yielded approximately 2 mg root exudate/g fresh root wt. Exudates contained four to six major components, with sorgoleone being the major component (> 85%). Three-dimensional structure analysis was performed to further characterize so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
150
1
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(159 citation statements)
references
References 16 publications
3
150
1
5
Order By: Relevance
“…Lynch 1977;Putnam and DeFrank 1983). However, the effects of allelochemicals in growing plants can be potent and long-lasting (Ben-Hammouda et al 1995;Czarnota et al 2001;Siegler 2006;Summers et al 2009). It is generally accepted that allelopathy results from the release of specific chemicals that influence such factors as seed germination, radicle and hypocotyl elongation, and seedling growth and development (Einhellig and Souza 1992;Geneve and Weston 1988;Weston 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Lynch 1977;Putnam and DeFrank 1983). However, the effects of allelochemicals in growing plants can be potent and long-lasting (Ben-Hammouda et al 1995;Czarnota et al 2001;Siegler 2006;Summers et al 2009). It is generally accepted that allelopathy results from the release of specific chemicals that influence such factors as seed germination, radicle and hypocotyl elongation, and seedling growth and development (Einhellig and Souza 1992;Geneve and Weston 1988;Weston 2005).…”
Section: Discussionmentioning
confidence: 99%
“…They include disruption of membrane permeability (Galindo et al, 1999), ion uptake (Lehman and Blum, 1999), inhibition of electron transport in both photosyntetic and the respiratory chain (Peñuelas et al, 1996;Abrahim et al, 2000;Czarnota et al, 2001), alterations of enzyme activities (Cruz-Ortega et al, 1990;Politycka, 1998), and inhibition of cell division (Cruz-Ortega et al, 1988;Anaya and Pelayo-Benavides, 1997). It has also been postulated that allelopathy stress might lead to an imbalance between antioxidant defenses and the amount of reactive oxygen species (ROS), resulting in oxidative stress (Cruz-Ortega et al, 2002;Bais et al, 2003;Romero-Romero et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Netzley et al (1988) reported that the concentration of sorgoleone exuded into the soil from S. bicolor roots can reach 10-100 μM. According to Czarnota et al (2001), the post-emergence application of sorgoleone inhibits the growth of various weeds, especially broad-leaf weeds, at the same concentration as the synthetic herbicide atrazine (0.6 kg a.i. ha −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is also an allelopathic species that represses the growth of numerous weeds, mainly the small-seeded species, due to exudates released by its roots, those exudates consisting mainly of sorgoleone, a biologically active lipid benzoquinone (Forney & Foy 1985;Netzly & Butler 1986;Meazza et al 2002;Dayan et al 2007;Marchi et al 2008;Albuquerque et al 2010). Sorgoleone (2-hydroxy-5-methoxy-3-[(8'Z,11'Z)-8' ,11' ,14'-pentadecatriene]-p-benzoquinone) is highly phytotoxic to broad-leaf and grass weeds at concentrations as low as 10 μM, affecting shoot growth with little or no effect on root growth (Einhellig & Souza 1992;Nimbal et al 1996;Czarnota et al 2001). The most active ingredients of sorgoleone reside in the 1,4-hydroquinone portion, which constitutively releases ~80-95% of the molecule (Dayan et al 2007;Albuquerque et al 2010).…”
Section: Introductionmentioning
confidence: 99%